Structure, Antigenic Properties, and Highly Efficient Assembly of PCV4 Capsid Protein - Wang, Dongliang; Mai, Jinhui; Lei, Bo; Zhang, Yingjie; Yang, Yi; Wang, Naidong (Frontiers in Veterinary Science, 2021)
Porcine circovirus type 4 (PCV4), a recently reported new circovirus, was first identified in a diseased pigs with clinical signs similar to porcine dermatitis nephropathy syndrome (PDNS), in Hunan province, China in 2019. More effort is needed to study the assembly of capsid protein (Cap) into virus-like particles (VLPs), and subsequently, its structure and antigenic properities in order to establish the solid foundation for diagnosis, vaccine design and biological study of PCV4. In this study, we expressed PCV4 Cap with a high-level in E. coli; this purified Cap is capable of self-assembling into VLPs (~ 20 nm) in vitro. Furthermore, this VLPs can be internalized by the PK15 and 3D4/21 cell lines. Of note, significant structure differences between PCV4 and PCV2 capsid were demonstrated among the loops (Loop BC, CD, DE, EF and GH), based on the 3D structure comparison. In addition, five potential B cell epitopes identified in silico were mostly located in surface-exposed loops of PCV4 capsid. The cross-reaction conferred by humoral immune responses between PCV4 and PCV2 or PCV3 was deemed unlikely, which was indicated by the assays of PCV4 or PCV2 VLPs based ELISA and western blotting. Our studies provide the new knowledge on PCV4 capsid surface patterns. Particularly, the PCV4 VLPs prepared in our study has significant potential to develop a novel vaccine and serological diagnostics for PCV4.